2015
DOI: 10.7861/clinmedicine.15-6-541
|View full text |Cite
|
Sign up to set email alerts
|

Sticks and stones: investigating rude, dismissive and aggressive communication between doctors

Abstract: Destructive communication is a problem within the NHS; however previous research has focused on bullying. Rude, dismissive and aggressive (RDA) communication between doctors is a more widespread problem and underinvestigated. We conducted a mixed method study combining a survey and focus groups to describe the extent of RDA communication between doctors, its context and subsequent impact. In total, 606 doctors were surveyed across three teaching hospitals in England. Two structured focus groups were held with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 16 publications
7
88
0
Order By: Relevance
“…1 They showed an improvement in compliance with the measures recorded before and after the introduction of the bundle. 1 They showed an improvement in compliance with the measures recorded before and after the introduction of the bundle.…”
Section: The Royal College Of Physicians' Fallsafe Care Bundles Applimentioning
confidence: 90%
See 1 more Smart Citation
“…1 They showed an improvement in compliance with the measures recorded before and after the introduction of the bundle. 1 They showed an improvement in compliance with the measures recorded before and after the introduction of the bundle.…”
Section: The Royal College Of Physicians' Fallsafe Care Bundles Applimentioning
confidence: 90%
“…1 The ephemeral, impersonal nature of a phone call and the lack of a pre-existing relationship between clinicians are both risk factors for rudeness. Our study was confined to communication within teaching hospitals but rude, dismissive and aggressive (RDA) communication is also likely to occur in non-teaching hospitals and across the primary-secondary care interface.…”
Section: Responsementioning
confidence: 99%
“…1 They showed an improvement in compliance with the measures recorded before and after the introduction of the bundle. This mirrors the RCP Fallsafe project itself.…”
Section: The Royal College Of Physicians' Fallsafe Care Bundles Applimentioning
confidence: 98%
“…This can be a negative experience. Residents in one United Kingdom study identified that 49% of their experiences of rude, dismissive or aggressive behaviour enacted towards them occurred in the context of interactions with other departments or specialties on behalf of their own team 5 . These boundary encounters contribute to identity development, as all encounters do, but in a negative way, positioning the resident as incompetent or useless, and as not belonging in the world of medicine.…”
mentioning
confidence: 99%